Epidemiology of Pediatric Acute Respiratory Distress Syndrome in Singapore: Risk Factors and Predictive Respiratory Indices for Mortality - Wong, Judith Ju-Ming; Loh, Tsee Foong; Testoni, Daniela; Yeo, Joo Guan; Mok, Yee Hui; Lee, Jan Hau (Frontiers in Pediatrics, 2014)
Aims: Acute respiratory distress syndrome (ARDS) represents the most severe form of acute lung injury .The aim of our study is to describe the epidemiology of pediatric ARDS in Singapore and compare the outcomes of ARDS using the following respiratory indices: PaO2/FiO2 ratio (P/F ratio), SpO2/FiO2 ratio (S/F ratio), oxygenation index (OI) and oxygen saturation index (OSI). Methods: We examined medical records of patients admitted to the Children’s Intensive Care Unit (CICU) in KK Women’s and Children’s Hospital from 2009 to 2012. Those who fulfilled criteria for the American-European Consensus Conference (AECC) definition for ARDS were identified. Demographic, clinical and radiographic information were extracted and analyzed. Results: We identified 70 patients with ARDS. Median age (interquartile range) was 6.2 (1.4, 10.4) years. The most common risk factor was pneumonia [50(71%)]. Overall mortality was 44 (63%) patients. 32 (56%) patients had an underlying chronic comorbidity; 18 (46%) were hematology-oncology conditions. 56 (80%) patients had multiorgan dysfunction. Adjunct therapies used in our patients included inhaled nitric oxide [5 (7%)], prone position [22 (31%)], steroids [26 (37%)] and neuromuscular blockade [26 (37%)]. A high OI and low PF ratio after 24 hours of diagnosis of ARDS were associated with mortality. From day 3 onwards, all four respiratory indices appropriately differentiated survivors from non-survivors. Severity based on the S/F ratio and OSI demonstrated association with decreased ventilator free days and ICU free days. Conclusion: Risk factors for mortality included having an underlying comorbidity, multiorgan dysfunction, a low PF ratio and high OI at 24 hours of ARDS. Abnormal SpO2 based measurements were reliable markers of poor outcomes in pediatric ARDS.